Pengenalan Erosi untuk Petani di Desa Cibeureum dan Kampung Nyomplong, Bandung - Shantosa Yudha Siswanto; Marenda Ishak Sonjaya Sule; Nadia N Kamaluddin; Ichsan Nurul Bari; Dani Lukman Hakim (Universitas Mathla'ul Anwar Banten, 2021)
INTRODUCING EROSION FOR FARMERS IN CIBEUREUM VILLAGE AND NYOMPLONG HAMLET BANDUNG. The upper part of the watershed is generally prone to erosion, because it is generally located in the hilly area. Due to this fact, effort to educate farmers must be taken to enhance the understanding of the farmerson conservation. Farmers from two villages has been selected as the object (Cibeureum Village, Kertasari District, Regency of Pangalengan and Nyomplong, Rajamandalakulon Village, Cipatat District, Regency of Bandung). The final aim of this effort is increasing a positive behavior related to the implementation of conservation. The method used in this activity is community service about the negative impact of erosion on the sustainability of their land. Based on the results of the pretest and postest quistionaire, a significant increment of 34% has resulted regarding the understanding of the farmer on the definition, process and the impact of erosion.